2016
DOI: 10.1002/rmv.1904
|View full text |Cite
|
Sign up to set email alerts
|

Saliviruses-the first knowledge about a newly discovered human picornavirus

Abstract: The salivirus, first discovered in the year 2009, is a member of the large and growing family Picornaviridae. At present, the genus Salivirus contains 1 species Salivirus A and 2 genotypes, Salivirus A1 and Salivirus A2. Salivirus has been identified in humans and chimpanzees and may cause acute gastroenteritis in humans, having been detected in 0% to 8.7% of fecal samples collected from gastroenteritis in different human populations. Salivirus is ubiquitous in wastewater of human origin and river water specim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 46 publications
1
13
0
1
Order By: Relevance
“…mNGS detected several recently discovered viruses (Saffold virus, salivirus A, WU polyomavirus, gemycircularvirus, and HPgV-2), representing their first detection in Vietnam and adding to the growing literature about the geographic distribution of these newly identified viruses. Salivirus A has been linked to gastrointestinal infection, and Saffold virus has been reported in gastrointestinal and respiratory infection patients (3437). Saffold virus has also been reported to be associated with myocarditis and aseptic meningitis (38, 39).…”
Section: Discussionmentioning
confidence: 99%
“…mNGS detected several recently discovered viruses (Saffold virus, salivirus A, WU polyomavirus, gemycircularvirus, and HPgV-2), representing their first detection in Vietnam and adding to the growing literature about the geographic distribution of these newly identified viruses. Salivirus A has been linked to gastrointestinal infection, and Saffold virus has been reported in gastrointestinal and respiratory infection patients (3437). Saffold virus has also been reported to be associated with myocarditis and aseptic meningitis (38, 39).…”
Section: Discussionmentioning
confidence: 99%
“…Eukaryotic viruses of the gastrointestinal microbiota. Adapted from [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. (a) This type of virus is also detected in healthy/asymptomatic hosts.…”
Section: What Types Of Viruses Are Found In the Gut?mentioning
confidence: 99%
“…Besides classic enteric viruses, recent studies have focused on the identification of emerging or newly identified viruses, e.g. polyomavirus, papillomavirus, Aichi viruses, saliviruses (Itta et al, 2016;Reuter et al, 2016) associated with water and wastewater. Enteric viruses are associated with a variety of diseases such as gastroenteritis, hepatitis, myocarditis, and meningitis in humans (Table 2).…”
Section: Virusesmentioning
confidence: 99%